Science parks, knowledge spillovers, and firms' innovative performance: evidence from Finland - Mariagrazia Squicciarini (Kiel Institute for the World Economy (IfW), 2009)
The paper focuses on the role of Science Parks (SPs) as seedbeds of innovation. It investigates whether and to what extent locating inside a science park relates to the innovative output of tenant firms. The simple assessment methodology proposed relies on count data models, uses patents as innovation performance indicators, and exploits original data regarding the Finnish science parks, their main characteristics, and the data of 252 SP tenant firms, including their patenting activity over the period 19702002. Among other results, the study suggests that both within and among SPs interaction and spillover effects exist, and points out the way in which they relate to firms' innovative output. Results are robust to controlling for the existence of innovation lags. Parks' first mover disadvantages also emerge, as well as non-negligible matching phenomena whereby firms' and parks' characteristics matter jointly.
Keywords: L29; O32; O38; 330; Science Parks; knowledge spillovers; innovation; patents; firm performance; Technologiezentrum; Innovation; Unternehmensentwicklung; Patent; Wissenstransfer; Finnland